Which Values Do Non-Native Marine Species Affect? A Case-Study Exploration of Perceived Values at Threat in Micronesia - Campbell, Marnie L.; Hewitt, Chad L. (Frontiers in Marine Science, 2018)
Impact assessment of non-native species introductions tend to focus on either economic and/or environmental risks. We present work that extends these approaches bringing environmental (ecological) and economic values together with social and cultural considerations. Our approach aims to better inform future non-native species management risk analyses. A triangulation approach involving literature and museum searches, face to face discussions, and questionnaires was undertaken to identify values perceived to be at risk with the arrival of non-native marine species in three countries in Micronesia (Guam, the Republic of Palau and Saipan). We identified value sets for a range of stakeholders and subsequently used scenario approaches to determine the values’ perceived relative worth (non-monetary) and directional change of worth following a biosecurity incursion. We identified 337 value sub-elements, of which at least 40% are thought to be at risk (their worth would diminish) if a non-native marine species introduction were to occur. Results were used to create Venn diagrams and value networks to aid in understanding the linkages between social, cultural, economic and environmental values. Additionally the relationship between elicited values and their alignment to Ecosystem Service contribution is identified and discussed. The Venn diagrams and value networks should prove a beneficial tool for understanding citizen concerns around perceived biosecurity risks and developing effective future biosecurity risk communication strategies.